Exploring the Dynamics of Parasocial Interactions with Hosts and Co-Viewers in Live-Streaming Shopping - Vidyanata, Deandra (Universitas Negeri Semarang, 2025)
In the last decade, a new era of social commerce has emerged, known as live streaming platforms, where consumers often build illusionary relationships known as Parasocial Interaction (PSI). While many scholars have explored various aspects of live-streaming shopping, they neglected both PSI with hosts and co-viewers. This study intends to bridge this gap by integrating these elements and investigating how they affect the Urge to Buy Impulsively (UBI) through Utilitarian Value (UV). The study population consists of Shopee live-streaming users, with a sample size of 400 respondents. The findings reveal that PSI with the host has no effect on UV or UBI, nor does UV mediate this connection. In contrast, PSI with co-viewers influences both UV and the UBI. Moreover, UV affects UBI and mediates the relationship between PSI with Co-Viewers and UBI. This study proves that illusionary interactions with co-viewers in live streaming can drive UBI by increasing the utilitarian value of the product through co-viewer validation. These results suggest that marketers should focus on fostering communities to enhance social proof in live-streaming.